2004
DOI: 10.1258/0004563042466802
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and laboratory features of calcium-sensing receptor disorders: a systematic review

Abstract: Mutations in the calcium-sensing receptor gene (CaSR) may result in disorders of calcium homeostasis manifesting as familial benign hypocalciuric hypercalcaemia (FBHH), neonatal severe hyperparathyroidism (NSHPT) or autosomal dominant hypocalcaemia with hypercalciuria (ADHH). FBHH may have a population prevalence as high as one in 16 000, and ADHH one in 70 000. NSHPT is very rare.The FBHH condition is usually asymptomatic. Parathyroidectomy does not result in normal serum calcium, and no active treatment is i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
67
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(69 citation statements)
references
References 119 publications
1
67
0
1
Order By: Relevance
“…4,5,14,17,18 The Ca/Cr clearance ratio is also used as a marker of hypercalciuria, where hypercalciuria cannot be excluded if the urinary creatinine concentration exceeds 40 mg/100 mL. 19,20 In the evaluation of PHPT, it is recommended that FHH be ruled out, even though this condition is very rare. Currently, if there is a strong suspicion for FHH, the presence of the CaSR gene mutation can be detected using readily available polymerase chain reaction techniques.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,5,14,17,18 The Ca/Cr clearance ratio is also used as a marker of hypercalciuria, where hypercalciuria cannot be excluded if the urinary creatinine concentration exceeds 40 mg/100 mL. 19,20 In the evaluation of PHPT, it is recommended that FHH be ruled out, even though this condition is very rare. Currently, if there is a strong suspicion for FHH, the presence of the CaSR gene mutation can be detected using readily available polymerase chain reaction techniques.…”
Section: Discussionmentioning
confidence: 99%
“…However, this should be reserved for cases in which treatment would be significantly altered based on the diagnosis. 5,7,14,15,19 Hypercalcemia increases eGFR; however, tubular resorption of calcium is altered by many other factors such as age, medications, and hormones. While the volume of urine collected can affect the urinary creatinine and calcium levels and could be affected by diuretic use, we did not specifically analyze these factors.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 Since mutational analysis of the CaSR gene became available, many individuals with hypocalcaemia have had their diagnosis revised. Lienhardt et al 12 reported a 42% prevalence of activating CaSR mutations in unrelated individuals with isolated hypoparathyroidism and Gunn and Gaffney 13 estimated the population prevalence of this condition to be one in 70,000.…”
Section: Discussionmentioning
confidence: 99%
“…In the clinical setting, the separation between FHH and PHPT is often based on the CCCR (20,41,42). We recommend a two-step diagnostic procedure in hypercalcemic patients with clinical suspicion of PHPT or FHH.…”
Section: Discussionmentioning
confidence: 99%